2022
DOI: 10.13057/biodiv/d230202
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Spanish mackerel’s diversity in Indonesian through local commodities in the fish market

Abstract: Abstract. Widayanti R, Nugroho HA, Megarani DV, Widiasih DA, Pakpahan S. 2021. Revealing Spanish mackerel’s diversity in Indonesian through local commodities in the fish market. Biodiversitas 23: 624-630. The objective of this study was to explore the diversity of Spanish mackerel in Indonesian Archipelago based on commodities offered in local fish markets. Eighteen specimens were collected from six different fish markets around the Indonesian archipelago. According to Wallace Line, the cytochrome B sequence w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Within Clade 3, individual mackerel fish from Fak-Fak, Papua, formed a close cluster with S. semifasciatus (NC021391 and JX559745). This finding aligns harmoniously with earlier research utilizing mtDNA Cyt gene sequences, establishing the close relationship between mackerel populations from Fak-Fak (Papua) and S. semifasciatus (Widayanti et al, 2022). It's important to note that S. semifasciatus, commonly known as gray mackerel, is an indigenous mackerel species found in the southern regions of Papua New Guinea and Northern Australia (Welch et al, 2015;Chaves and Birnfeld, 2023).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Within Clade 3, individual mackerel fish from Fak-Fak, Papua, formed a close cluster with S. semifasciatus (NC021391 and JX559745). This finding aligns harmoniously with earlier research utilizing mtDNA Cyt gene sequences, establishing the close relationship between mackerel populations from Fak-Fak (Papua) and S. semifasciatus (Widayanti et al, 2022). It's important to note that S. semifasciatus, commonly known as gray mackerel, is an indigenous mackerel species found in the southern regions of Papua New Guinea and Northern Australia (Welch et al, 2015;Chaves and Birnfeld, 2023).…”
Section: Discussionsupporting
confidence: 85%
“…The closest genetic distance was observed between the mackerel fish populations from Palembang and Rembang, while the furthest distance existed between Cilacap and Fak-Fak (Papua) populations. It's worth noting that a previous study using mtDNA Cyt b gene sequences reported genetic distances of 0.000-0.018 between mackerel fish populations from Palembang and Rembang, and 0.175-0.178 between populations from Cilacap and Papua (Widayanti et al, 2022). Our research also delved into the amino acid patterns among population groups.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…One of the potential fishery products from Indonesia is mackerel, a species of marine fish with a particular flavor that is popular in Indonesian society. This pelagic fish is found in almost all marine areas of Indonesia (Widayanti et al 2022). Mackerel in Indonesia has been processed into many local foods such as dumplings, otakotak, and empek-empek.…”
Section: Introductionmentioning
confidence: 99%